Collagenous colitis: Requirement for high-dose budesonide as maintenance treatment. Issue 9 (September 2017) - Fernandez-Bañares, Fernando; Piqueras, Marta; Guagnozzi, Danila; Robles, Virginia; Ruiz-Cerulla, Alexandra; Casanova, María José; Gisbert, Javier P.; Busquets, David; Arguedas, Yolanda; Pérez-Aisa, Angeles; Fernández-Salazar, Luis; Lucendo, Alfredo J.; et al.
Abstract: Background: Controlled studies show high efficacy of budesonide in inducing short-term clinical remission in collagenous colitis (CC), but relapses are common after its withdrawal. Aim: To evaluate the need for high-dose budesonide (≥6 mg/d) to maintain clinical remission in CC. Methods: Analysis of a multicentre retrospective cohort of 75 patients with CC (62.3 ± 1.5 years; 85% women) treated with budesonide in a clinical practice setting between 2013 and 2015. Frequency of budesonide (9 mg/d) refractoriness and safety, and the need for high-dose budesonide to maintain clinical remission, were evaluated. Drugs used as budesonide-sparing, including azathioprine and mercaptopurine, were recorded. Logistic regression analysis was performed to evaluate the risk factors associated with the need for high-dose budesonide (≥6 mg/d) to maintain clinical remission. Results: Budesonide induced clinical remission in 92% of patients, with good tolerance. Fourteen of 68 patients (21%; 95% CI, 13–32%) needed high-dose budesonide to maintain remission. Only intake of NSAIDs at diagnosis (OR, 8.6; 95% CI, 1.6–44) was associated with the need for high-dose budesonide in the multivariate analysis. Treatment: with thiopurines was effective in 5 out of 6 patients (83%; 95% CI, 44–97%), allowing for withdrawal from or a dose decrease of budesonide. Conclusions: One fifth of CC patients, especially those with NSAID intake at diagnosis, require high-dose budesonide (≥6 mg/d) to maintain clinical remission. In this setting, thiopurines might be effective as budesonide-sparing drugs.